The Relationship Between Spiritual Intelligence and Prosocial Behavior in Level III Students Of Nursing Study Program Santa Elisabeth College Of Health Sciences Medan 2024 - Imelda Derang; Lindawati Simorangkir; Naomi Trinita Pangaribuan (Jurnal Kesehatan Amanah, 2024)
Prosocial behavior is an action to share, cooperate, contribute, help, dare to be honest, be generous and consider the rights and welfare of others, therefore good spiritual intelligence is needed in overcoming every problem and interpreting every life, which is marked by the ability to a person to love and appreciate themselves and others, and understand the deepest feelings of the people around them. This research aims to identify the relationship between spiritual intelligence and prosocial behavior in third year students of the Nursing Study Program at Santa Elisabeth College of Health Sciences, Medan 2024. This research design uses a correlational design with a cross sectional approach, the sampling technique uses Total Sampling with a total sample of 86 respondents . The instruments used are spiritual intelligence and prosocial behavior questionnaire sheets. The research results show that the majority of students' spiritual intelligence at Level III of Nursing Study Program is in the high category, 61 people (70.9%) and the majority of their prosocial behavior is in the moderate category, 76 people (88.4%). The Spearman Rank statistical test obtain a p-value of 0.047 (p<0.05) so it can be concluded that there is a relationship between spiritual intelligence and prosocial behavior. The researcher suggests that future researchers pay more attention to the factors that influence prosocial behavior.